2016
DOI: 10.1021/acs.jpcc.6b03560
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Mass Transport and Spatially Heterogeneous Flux Processes for in Situ Atomic Force Microscopy Measurements of Crystal Growth and Dissolution Kinetics

Abstract: It is well-established that important information about the dissolution and growth of crystals can be obtained by the investigation of step movement on single crystal faces via in-situ AFM.However, a potential drawback of this approach for kinetic measurements is that the small region of investigation may not be representative of the overall surface. It is shown that the investigation of local processes without accounting for the processes outside the region of interest can lead to significant misinterpretatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 68 publications
(241 reference statements)
0
21
1
Order By: Relevance
“…, ratio of the activity product to the gypsum solubility product) of about 0.5. However, the flow velocity of 0.47 mm s −1 measured in the current study is nearly five times greater than that simulated by Peruffo et al (2016). In addition, the absence in this study of a physical obstruction near the surface likely makes the flowing fluid more effective at removing dissolved nearsurface components.…”
Section: Resultscontrasting
confidence: 58%
See 3 more Smart Citations
“…, ratio of the activity product to the gypsum solubility product) of about 0.5. However, the flow velocity of 0.47 mm s −1 measured in the current study is nearly five times greater than that simulated by Peruffo et al (2016). In addition, the absence in this study of a physical obstruction near the surface likely makes the flowing fluid more effective at removing dissolved nearsurface components.…”
Section: Resultscontrasting
confidence: 58%
“…The hydrodynamics within a fluid cell are complex (Gasperino et al, 2006; Peruffo et al, 2016), and in the case of in situ AFM the presence of the physical probe can cause local changes in flow velocity. In at least one in situ AFM study of gypsum, the flow perturbation was severe enough that actively dissolving sites in neighboring regions affected the topography changes and dissolution flux in the field of view (Peruffo et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the rate of removal of ions by diffusion or advection from the surface is sufficiently low, then the concentration near the surface could increase to a significant fraction of the saturation point and the process could become kinetically controlled by mass transport. Reaction-transport simulations near an AFM tip at a dissolving gypsum surface by Peruffo et al (2016) indicated that calcium and sulfate concentrations decreased by about 50% when the liquid flow increased from zero to only 0.1 mm s −1 . In this paper, the flow velocity near the surface is nearly five times greater than that.…”
Section: Experimental Methodsmentioning
confidence: 99%